DIGITAL INNOVATION IN BUSINESS AND ECONOMY: COLLABORATION OF BACK-OFFICE AND FRONT-OFFICE EMPLOYEES WITH ADVANCED TECHNOLOGY IN FACILITATING SEAMLESSNESS SERVICE QUALITY DELIVERY IN HOTEL INDUSTRY (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
The main objective of this research is to investigate how back-office and front-office employees in collaboration with advanced technology facilitate seamlessness in the hotel industry. A constructivist research paradigm is employed while effectively utilizing mixed methodology. The research adopts a multiple-case study design, focusing on two hotels; a five-star hotel and a three-star hotel, both located in Yogyakarta, Indonesia. SPSS data analysis tool will be applied to diverse primary and secondary data sources, including interviews, focus group discussions, survey questionnaires, and online customer survey reports from each hotel's official website and social media platforms such as Instagram. Additionally, the seamless hotel organization theoretical framework is employed for this study as a roadmap towards data collection, analysis, and interpretation, guiding the investigation of the study. By analyzing and comparing the strategies, challenges, and opportunities in both hotels, the study has revealed or discovered the importance of effective collaboration of back-office & front-office employees with advanced technology in every hotel in enhancing seamlessness hotel service operations. The findings reveal that there is effective collaboration of back-office and front-office employees with advanced technology in facilitating a sustainable seamlessness service quality delivery in hotel industry.
Keywords: Seamlessness; Advanced-technology; Hotel industry; Front-office; Back-office